The safety and feasibility of minimally invasive plate osteosynthesis (MIPO) on the medial side of the femur: A cadaveric injection study - C. Jiamton (2018)
© 2015 Elsevier Ltd. All rights reserved. Introduction Minimally invasive plate osteosynthesis (MIPO) on the medial side of the femur appears to be a dangerous procedure due to possible femoral artery injury. Objective This study aims to determine the feasibility of applying MIPO of the femur via the medial approach, and to determine the anatomical relationship and structures at risk between the artery and the implant using computed tomography angiography. Materials and methods A descriptive study of ten fresh cadavers was done. Two separate incisions were made, creating a submuscular tunnel close to the medial side of the femur. An 11- or 13-hole LCP lateral proximal tibial plate (5.0 mm) was inserted through the distal incision into the submuscular tunnel and fixed. A CT angiogram with 3D reconstruction was made to determine the distance from and location of the plate relative to the femoral artery and surgical dissection was done to identify the structures at risk. Results No disruptions of superficial or deep femoral arteries were found. The closest distances from the superficial femoral artery and deep femoral artery to the plate were 8.3-27.2 mm (average 16.3 mm) (99% CI: 12.7-19.9) at the level 3 and 4.5-20.0 mm (average 8.6 mm) (99% CI: 6.4-10.9) at the level 2 in the proximal part of femur, respectively. The location where the SFA crossed the anterior cortex of the femur in the sagittal plane was 9.7-36.0% of the femoral length (average 20.1%) (99% CI: 15.0-25.3%) and the posterior cortex of the femur was 24.7-55.3% of the femoral length (average 40.8%) (99% CI: 35.0-46.7%). The location where the DFA crossed the anterior cortex of the femur in the sagittal plane was 7.9-25.3% of the femoral length (average 13.4%) (99% CI: 10.6-16.3%) and where it crossed the posterior cortex of the femur was 21.7-39.4% of the femoral length (average 31.2%) (99% CI: 27.1-33.3%). Conclusion MIPO of the femur via medial approach is a feasible option for treatment of femoral fractures when the lateral approach is contraindicated. The distal 60% of the femoral length is safe for this approach.